2012
DOI: 10.1111/j.1439-0396.2012.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the feeding of eventing horses during competition

Abstract: This study aims at the comparison of the actual feeding of horses with the recommendations from the literature, and it studies the effects of feeding and exercise on several blood metabolic parameters before and after exercise. Blood samples were collected from 25 horses during one-star eventing competitions and evaluated for blood glucose, insulin, lactate, free fatty acids and triglyceride levels. Questionnaires on the feeding practices of the horses were evaluated. The questionnaires revealed that during tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The findings report similar levels of feed intake as reported in other elite groups of sport horses [8][9][10], but also highlight a need for representatives to be mindful of feed selection when traveling to different venues where different feeds are available.…”
Section: Discussionsupporting
confidence: 86%
“…The findings report similar levels of feed intake as reported in other elite groups of sport horses [8][9][10], but also highlight a need for representatives to be mindful of feed selection when traveling to different venues where different feeds are available.…”
Section: Discussionsupporting
confidence: 86%
“…Data had to be converted from μg/L into the commonly used SI unit μIU/mL to compare the results from ELISA with results derived from RIA and CLIA. In previous studies in which insulin analysis had been performed with the equine-optimized porcine-specific ELISA, data was either presented in μg/L [9, 10, 18] or converted into mU/L [19]. In the latter case, conversion was performed without an exact statement regarding the conversion factor, which was suggested to be 10 in an earlier publication by the same author [9].…”
Section: Discussionmentioning
confidence: 99%
“…Only one enzyme-linked immunosorbent assay (ELISA) advertised by the manufacturer as being specific for measuring equine insulin is commercially available1, and this is based on anti-porcine insulin antibodies. This assay has been validated for use in horses [8] and has already been used successfully in several studies [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, plasma aldosterone concentration was reduced in horses in training when consuming diets with low amounts of sodium [12]. On the other hand, eventing horses receiving no or ‘inadequate’ amounts of additional NaCl supplementation showed persistent good performance and apparently undisturbed health [13]. It has been reported that the voluntary intake of NaCl ([12]: 0–62 mg/kg bwt.d) is frequently lower than required to meet the currently recommended intakes for horses in work [12] although it might be sufficient for those in little or no work [14].…”
Section: Introductionmentioning
confidence: 99%